PSYCHOLOGICAL ASPECTS OF ADAPTATION TO THE MILITARY TRAINING PROCESS (European Journal of Pedagogical Initiatives and Educational Practices, 2026)
This article examines the issue of adaptation to military activity. The adaptation process of military personnel is analyzed. A comparative analysis of the scientific definitions of the term “adaptation” is conducted.